Pengaruh Honor Guru terhadap Keaktifan Mengajar Guru Madrasah Diniyah Al-Barakah Rombiya Timur Tahun 2022 - Abdillah, Abdillah; Shulhan, Shulhan (Alhamra Jurnal Studi Islam, 2023)
In improving the performance and activeness of teachers in teaching and learning activities in educational institutions, there needs to be encouragement for all parties in this case researchers focus more on educators in the form of salaries or honors for private teachers, be it daily salaries, weekly or monthly salaries, therefore the honor given to teachers of religious schools Al-Barakah Rombiya Timur aims to motivate the spirit of active teaching of teachers. The approach used by researchers today is a quantitative approach with data collection techniques using questionnaires and documentation methods. The subject of this study was the teacher of religious schools Al-Barakah Rombiya Timur. The data analysis techniques that researchers use are data collection, data presentation, instrument testing, validity and reliability, and ending with drawing conclusions. This study is a type of correlation research that uses sampling type techniques, whose number of respondents is 15 people out of 30 teachers. From the results of data analysis collected using simple linear regression with the help of SPSS 24.0 software, the numbers obtained t count 1.199 with significant numbers 0.250<0.05 and r count 0.305. After consultation with r the table at N=16, with a confidence interval level of 5%= 0.497. It is concluded that the influence of teacher honor on the teaching activity of teachers of religious schools Al-Barakah Rombiya Timur is categorized as Low.